D Studi Deskriptif: Karakteristik Perilaku Pencarian Informasi Pengguna Layanan Poli Ortopedi Rumah Sakit Islam Surabaya A. Yani Tahun 2023: Karakteristik Perilaku Pencarian Informasi Pengguna Layanan Poli Ortopedi Rumah Sakit Islam Surabaya A. Yani Tahun 2023 - Donny Permana; Pipit Festi Wiliyanarti; Mundakir Mundakir; Annisa Nurida (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
When making decisions about disease screening, prevention, and treatment, seeking health information is essential. Access to and methods of obtaining health information are impacted by digital transformation, including in the orthopedics sector. This study aimed to determine the sources of information used by patients at Surabaya Islamic Hospital (RSI) and how patients choose media related to orthopedic services. This study is a quantitative, descriptive, observational study involving 102 respondents and conducted in June 2024. Primary data were collected through a questionnaire covering 25 questions about treatment choices, media exposure, media satisfaction, and social demographics, which will later be analyzed using Microsoft Excel and SPSS. In this study, most respondents (279 vs. 228) sought orthopedic information through contemporary media. The most common sources of conventional and contemporary media were Instagram (47,1%) and family (55,9%), respectively. Conventional media accounted for the longest media usage duration (≤ 1 hour per day; 69,7% vs 62,0%). Conventional media were used more frequently (76,8% vs 74,2%) - two to four times a day. Conventional media use was more frequent among respondents (57,9% vs 50,9%). Conventional media were found to be more satisfactory in terms of education, ease of interaction, and information search. In conclusion, Contemporary media offers higher satisfaction levels when seeking orthopedic information, despite conventional media being used more frequently. These findings emphasize the importance of considering both forms of media when marketing.